The difficult airway with recommendations for management – Part 2 – The anticipated difficult airway - Law, J. Adam; Broemling, Natasha; Cooper, Richard M.; Drolet, Pierre; Duggan, Laura V.; Griesdale, Donald E.; Hung, Orlando R.; Jones, Philip M.; Kovacs, George; Massey, Simon; Morris, Ian R.; Mullen, Timothy; et al. (Canadian journal of anesthesia, 2013)
Background Appropriate planning is crucial to avoid morbidity and mortality when difficulty is anticipated with airway management. Many guidelines developed by national societies have focused on management of difficulty encountered in the unconscious patient; however, little guidance appears in the literature on how best to approach the patient with an anticipated difficult airway. Methods To review this and other subjects, the Canadian Airway Focus Group (CAFG) was re-formed. With representation from anesthesiology, emergency medicine, and critical care, CAFG members were assigned topics for review. As literature reviews were completed, results were presented and discussed during teleconferences and two face-to-face meetings. When appropriate, evidence- or consensus-based recommendations were made, and levels of evidence were assigned. Principal findings Previously published predictors of difficult direct laryngoscopy are widely known. More recent studies report predictors of difficult face mask ventilation, video laryngoscopy, use of a supraglottic device, and cricothyrotomy. All are important facets of a complete airway evaluation and must be considered when difficulty is anticipated with airway management. Many studies now document the increasing patient morbidity that occurs with multiple attempts at tracheal intubation. Therefore, when difficulty is anticipated, tracheal intubation after induction of general anesthesia should be considered only when success with the chosen device(s) can be predicted in a maximum of three attempts. Concomitant predicted difficulty using oxygenation by face mask or supraglottic device ventilation as a fallback makes an awake approach advisable. Contextual issues, such as patient cooperation, availability of additional skilled help, and the clinician’s experience, must also be considered in deciding the appropriate strategy. Conclusions With an appropriate airway evaluation and consideration of relevant contextual issues, a rational decision can be made on whether an awake approach to tracheal intubation will maximize patient safety or if airway management can safely proceed after induction of general anesthesia. With predicted difficulty, close attention should be paid to details of implementing the chosen approach. This should include having a plan in case of the failure of tracheal intubation or patient oxygenation.